Beryllium and its inorganic compounds – Determination of beryllium in urine by atomic absorption spectrometry [Biomonitoring Methods, 2017]. Issue 4 (27th October 2017) - Paul, R.; Budnik, L.T.; Göen, T.; Hartwig, A.; ,
Abstract: The working group „Analyses in Biological Materials" of the Permanent Senate Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area verified the present biomonitoring method. This procedure describes a method for the determination of beryllium in urine by means of atomic absorption spectrometry using the graphite furnace technique with a pyrolytically coated graphite tube and Zeeman background correction. The acidified samples are homogenised and injected into the graphite tube without further sample preparation using an autosampler. Magnesium nitrate is used as a matrix modifier. After drying, pyrolysis and atomisation, the absorbance is measured at 234.9 nm. The beryllium concentration is quantified using either a calibration curve (method I) or the standard addition method (method II). The method was extensively validated and the reliability data were confirmed by independent laboratories, which have established and cross‐checked the whole procedure.